Generation of a Spiral Ganglion Neuron Degeneration Mouse Model - Hu, Zhengqing; Komal, Fnu; Singh, Aditi; Deng, Meng (Frontiers in Cell and Developmental Biology, 2021)
Spiral ganglion neurons (SGNs) can be injured by a wide variety of insults. However, there still is a lack of degeneration models to specifically damage the SGNs without disturbing other types of cells in the inner ear. This study aims to generate an SGN-specific damage model using the Cre-LoxP transgenic mouse strains. The Cre-inducible diphtheria toxin receptor (iDTR+/+) knock-in mouse strain was crossed with a mouse strain with Cre activity specific to neurons (NeflCreER/CreER). Expression of the Cre-recombinase activity was evaluated using the reporter mouse strain Ai9 at pre-hearing, hearing onset, and post-hearing stages. Accordingly, heterozygous NeflCreER/+;iDTR+/– mice were treated with tamoxifen on postnatal days 1–5 (P1–5), followed by diphtheria toxin (DT) or vehicle injection on P7, P14, and P21 to evaluate the SGN loss. Robust tamoxifen-induced Cre-mediated Ai9 tdTomato fluorescence was observed in the SGN area of heterozygous NeflCreER/+;Ai9+/– mice treated with tamoxifen, whereas vehicle-treated heterozygote mice did not show tdTomato fluorescence. Compared to vehicle-treated NeflCreER/+;iDTR+/– mice, DT-treated NeflCreER/+;iDTR+/– mice showed significant auditory brainstem response (ABR) threshold shifts and SGN cell loss. Hair cell count and functional study did not show significant changes. These results demonstrate that the NeflCreER/CreER mouse strain exhibits inducible SGN-specific Cre activity in the inner ear, which may serve as a valuable SGN damage model for regeneration research of the inner ear.